1990
DOI: 10.1002/hep.1840120518
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of tumor necrosis factor-α in development of hepatic injury in galactosamine-sensitized mice

Abstract: Intravenous injection of lipopolysaccharide and D-galactosamine, at doses of 0.2 micrograms/kg and 800 mg/kg, respectively, elicited massive hepatic necrosis within 24 hr in C3H/HeN mice. The plasma L-alanine aminotransferase (ALT, E.C. 2.6.1.2) or L-aspartate aminotransferase (AST, E.C. 2.6.1.1) activities at this point reached more than 2,000 IU/L. However, overt hepatic injury as evaluated by the plasma aminotransferase activities did not develop in mice in which only lipopolysaccharide or only D-galactosam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 15 publications
4
88
0
Order By: Relevance
“…TNF-␣ is a key mediator in LPS/GalN-induced murine ALF 11,19 ; therefore, we assessed whether production of TNF-␣ is similar in Ron TK Ϫ/Ϫ mice compared with Ron TK ϩ/ϩ mice. Serum TNF-␣ levels were assessed at hourly time intervals after injection of LPS/GalN (Fig.…”
Section: Ron Tk ؊/؊ Mice Have a Protected Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-␣ is a key mediator in LPS/GalN-induced murine ALF 11,19 ; therefore, we assessed whether production of TNF-␣ is similar in Ron TK Ϫ/Ϫ mice compared with Ron TK ϩ/ϩ mice. Serum TNF-␣ levels were assessed at hourly time intervals after injection of LPS/GalN (Fig.…”
Section: Ron Tk ؊/؊ Mice Have a Protected Liver Injurymentioning
confidence: 99%
“…[9][10][11] LPS-induced effects on Kupffer cells, the resident macrophage population of the liver, play a prominent role in many human liver disease processes, including ALF. [12][13][14] LPS stimulates Kupffer cells to release tumor necrosis factor ␣ (TNF-␣) 15,16 as well as a cohort of additional inflammatory cytokines such as interleukin 6 (IL-6), IL-10, and interferon gamma (IFN-␥).…”
mentioning
confidence: 99%
“…TNF-␣-induced hepatocyte apoptosis is the main event in this model. 6,9 TNF receptor I in hepatocytes transduces apoptotic signals through a cytoplasmic death effector domain. 10,11 In one apoptotic pathway, activation of caspase-8 through interaction of TRADD with FADD/MORT1 leads to sequential activation of ICE (caspase-1) and CPP32 (caspase-3).…”
Section: Hgf Suppressed Activation Of Cpp32 (Caspase-3) Protease In Thementioning
confidence: 99%
“…7 Because rodents are more than 1,000-fold less sensitive toward LPS than humans, sensitization by D-galactosamine (GalN) together with LPS injection has been often used as an animal model of fulminant hepatic failure. 6,8,9 Mice treated with a combination of LPS ϩ GalN selectively develop hepatic failure, which is much more severe and more rapid than fulminant hepatic failure in humans, as well as liver injury in the mice, as induced by a high dose of LPS alone, without sensitization. 6,7 Studies showed that tumor necrosis factor ␣ (TNF-␣)-induced massive hepatocyte apoptosis is a predominant mechanism functioning in this model, while complex factors are involved like fulminant hepatic failure in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation